2016
DOI: 10.1209/0295-5075/116/17001
|View full text |Cite
|
Sign up to set email alerts
|

Inertia effects in the real-time dynamics of a quantum spin coupled to a Fermi sea

Abstract: -Spin dynamics in the Kondo impurity model, initiated by suddenly switching the direction of a local magnetic field, is studied by means of the time-dependent density-matrix renormalization group. Quantum effects are identified by systematic computations for different spin quantum numbers S and by comparing with tight-binding spin-dynamics theory for the classical-spin Kondo model. We demonstrate that, besides the conventional precessional motion and relaxation, the quantum-spin dynamics shows nutation, simila… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Using the time-dependent density-matrix renormalization group (t-DMRG, see Refs. [32,38,39]), we have also qualitatively verified the effect for L > 1 in the quantum-spin case, see Fig. 1 ("quantum").…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Using the time-dependent density-matrix renormalization group (t-DMRG, see Refs. [32,38,39]), we have also qualitatively verified the effect for L > 1 in the quantum-spin case, see Fig. 1 ("quantum").…”
supporting
confidence: 75%
“…Damping and finally relaxation S(t) → Sẑ is phenomenologically described by the LLG equation [27] and is also found microscopically from the model (2) for J > 0 [19,21,23,29]. Besides precession and damping, the electronic system causes a weak nutation of the spin [30][31][32]. While damping ∝Ṡ and nutation ∝S are higher-order effects [33], spin precession is the most elementary phenomenon in this context.…”
mentioning
confidence: 93%
“…An important question concerns the conditions for which the constraints (3) are (approximately) satisfied. Previous work on spin dynamics in the s-d impurity model [43][44][45][46] has shown that the real-time evolution of the classical spin is almost adiabatic in large regions of parameter space. It is thus tempting to expect almost adiabatic motion in a certain parameter range and hence an anomalous precession frequency, as predicted by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…In the RKKY case, it is the ground-state magnetic susceptibility χ 12 (ω = 0) that determines the RKKY effective interaction. Besides this, full linearresponse theory and ground-state response functions also describe other effects, such as Gilbert damping or inertia effects [20,21,[24][25][26][27], but those come at higher order in an expansion in the typical memory time scale and can thus be classified as being of secondary importance.…”
Section: Introductionmentioning
confidence: 99%